Collaboration between Parents and Kindergarten Teachers - Goshen, Oranit (Wydawnictwo Naukowe UAM, 2016)
Educators frequently point out the critical role of the home and family environment in determining children’s kindergarten success, and it appears that the earlier this influence takes place, the greater the likelihood of the child’s higher achievement. In order for parents to get more involved with children’s education, a better communication must be established between parents and teachers in kindergartens. Effective communication between families and kindergartens is frequent and bidirectional, instills a sense of shared purpose, and works toward mutually advantageous solutions to problems. The aim of this paper is to build and effective communication system between teachers and parents in the kindergarten. Therefore, the current work will focus on the collaboration between teachers and parents, which consists in two main elements: (1) Partnership which presents the parties involved with special challenges that must be navigated unto agreement. (2) Communication which is defined as working level of partnership, e.g. activity of conveying information through the exchange of ideas, feelings, intentions, attitudes, expectations, perceptions or commands.
Współpraca rodziców z nauczycielami w przedszkolach
Keywords: teachers; kindergarten; parents; collaboration